Critical evaluation and thermodynamic modeling of the Fe–P and Fe–C–P system. (September 2020) - Bernhard, Michael; Kang, Youn-Bae; Presoly, Peter; Gheribi, Aimen E.; Bernhard, Christian
Abstract: Phosphorus is known to be a strongly segregating element in steel; even small amounts influence the solidification phenomena and product quality during casting processes. In order to provide an accurate prediction tool for process control in steelmaking, a CALPHAD-type thermodynamic optimization of the Fe–C–P system was performed including modeling of the binary Fe–P subsystem. The liquid phase was modeled using the Modified Quasichemical Model (MQM) in the pair approximation, which generally yields better results for strong short-range ordering (SRO) tendency in the solution. The solid bcc and fcc solutions were described using the Compound Energy Formalism (CEF). In addition, ab-initio calculations were performed to estimate the enthalpies of formation of the corresponding end-member for fcc and bcc, respectively. The phosphides Fe3 P, Fe2 P and FeP were treated as stoichiometric compounds. Higher order phosphides were not considered, since there is no reliable experimental information available in literature. The present model successfully reproduces most of the literature data within the experimental uncertainty in the Fe–C–P system without introducing a ternary parameter for the liquid phase. Compared with previous thermodynamic assessments, the agreement with recently published thermal analysis measurements of Fe–P and Fe–C–P alloys is significantly improved.